Factors Affecting Customer's Purchase Decision while Shopping on Tiktok Live: Impulsive Buying as a Moderator - Puspa Novita Sari; Lorena Dara Putri Karsono (Relevance: Journal of Management and Business, 2023)
Business development in the digital era is now starting to shift not only by selling products in online stores such as marketplaces but also by utilizing social media through live streaming features. Live streaming on the TikTok application allows consumers to directly see the products offered and interact with sellers. This study analyzes what factors influence consumer purchasing decisions when viewing live streaming on the Tiktok application. Respondents in this study were consumers who made purchases through live streaming on the Tiktok application as many as 173 respondents. Measurement of research results was tested using the Structural Equation Model (SEM) based on Partial Least Square (PLS). The results of the study show that scarcity messaging and hedonic shopping motivation influence impulsive buying. In addition, impulsive buying mediates the relationship between scarcity messaging and purchase decisions, and impulsive buying also mediates the relationship between hedonic shopping motivation and purchase decisions. The results of this study can be used by business people to analyze the factors that influence purchasing decisions so that they are expected to be able to increase sales when live streaming takes place.